Space development and space science together, an historic opportunity. (August 2016) - Metzger, Philip T.
Abstract: The national space programs have an historic opportunity to help solve the global-scale economic and environmental problems of Earth while becoming more effective at science through the use of space resources. Space programs will be more cost-effective when they work to establish a supply chain in space, mining and manufacturing then replicating the assets of the supply chain so it grows to larger capacity. This has become achievable because of advances in robotics and artificial intelligence. It is roughly estimated that developing a lunar outpost that relies upon and also develops the supply chain will cost about 1/3 or less of the existing annual budgets of the national space programs. It will require a sustained commitment of several decades to complete, during which time science and exploration become increasingly effective. At the end, this space industry will capable of addressing global-scale challenges including limited resources, clean energy, economic development, and preservation of the environment. Other potential solutions, including nuclear fusion and terrestrial renewable energy sources, do not address the root problem of our limited globe and there are real questions whether they will be inadequate or too late. While industry in space likewise cannot provide perfect assurance, it is uniquely able to solve the root problem, and it gives us an important chance that we should grasp. What makes this such an historic opportunity is that the space-based solution is obtainable as a side-benefit of doing space science and exploration within their existing budgets. Thinking pragmatically, it may take some time for policymakers to agree that setting up a complete supply chain is an achievable goal, so this paper describes a strategy of incremental progress. The most crucial part of this strategy is establishing a water economy by mining on the Moon and asteroids to manufacture rocket propellant. Technologies that support a water economy will play an important role leading toward space development.